Improving physician well‐being and reducing burnout using a peer‐to‐peer recognition program - Chang, Jenny; Saggar, Vinay; Cortijo‐Brown, Alexis; Friedman, Benjamin W.; Jones, Michael; Li‐Sauerwine, Simiao; Rebillot, Katie; Corbo, Jill (AEM education and training, 2023)
Background Drivers of physician burnout include an intricate interplay between health care organizational structures, societal influences, and individual‐level factors. In the traditional workforce, peer‐to‐peer recognition programs (PRPs) have reduced burnout by building a sense of community and effectively creating a “wellness culture.” We implemented a PRP in an emergency medicine (EM) residency and determined its impact on subjective symptoms of burnout and wellness. Methods This was a prospective, pre‐ and postintervention study conducted in a single residency over a 6‐month period. All 84 EM residents of the program were sent a voluntary anonymized survey that included a validated instrument on wellness and burnout. A PRP was initiated. After 6 months, a second survey was distributed. The outcome of the study was to examine whether the addition of a PRP reduced burnout and improved wellness. Results There were 84 respondents to the pre‐PRP survey and 72 to the post‐PRP survey. Respondents reported an improvement after the inception of the use of the PRP in two factors that contribute to a physician's wellness: feeling recognized for accomplishments at work, which improved from 45% (38/84) affirmative to 63% (45/72; 95% confidence interval [CI] 2.3%–32.4%, p = 0.025) and a comfortable and supportive work environment, which improved from 68% (57/84) to 85% (61/72; 95% CI 3.5%–29.3%, p = 0.014). There was no significant effect in the Stanford Professional Fulfillment Index (PFI) as a result of this intervention over the 6 months. Conclusions A PRP initiative resulted in improvements in several factors that drive physician wellness but overall burnout measured by the Stanford PFI did not show any improvement over the 6‐month period. A future longitudinal study examining the continuous assessment of PRP on the EM residents throughout the entire course of 4 years of residency training would be beneficial to determine if it could change burnout from year to year.